Detection of Fluorescently Labeled Carbohydrate-Deficient Transferrin, a Marker of Alcohol Dependence, in Dried Blood Spots - Zhang, Binxue; Huang, Mengting; Zheng, Zhiye; Yu, Suhong; Rehman, Aikebaier (Transactions on Materials, Biotechnology and Life Sciences, 2024)
A fluorescence-based (HPLC-FLD) method was developed for the detection of carbohydrate-deficient transferrin (CDT), a marker of alcohol dependence, in dried blood spots (DBS). Dried blood spots were cut and immersed in hydrochloric acid to leach out proteins, labeled with terbium ions, and then sent to high-performance liquid chromatography coupled with a fluorescence detector for detection. The levels of CDT in the dried blood spot samples of 10 clinically alcohol-dependent individuals were in general agreement with the results of the assayed levels of CDT in serum samples from the same source. The method can effectively amplify the detection signal of micro samples with high sensitivity and specificity, and the sampling method is simple and convenient to ensure the accuracy of the results, which is suitable for the qualitative and quantitative analysis of CDT in clinical micro samples.